The Concept of Fashion Trend: meaning, history, connotation (ModaPalavra e-periódico, 2018)
With the intention of contributing to the theoretical deepening of trend studies, the present research aims to understand the historical origins and transformations of the term trend and, more specifically, the fashion trend. The methodological procedure involved a consistent bibliographical review. Firstly, we investigated the etymology of the term in Portuguese, English, and German.  In addition, we combined different consolidated bibliographical references - such as Caldas, Lindkvist, and Vejlgaard - in order to historically understand the concept and its applicability.  The general interpretation of the term tendency relates to a force that leads to a finite but uncertain future. Between 1946 and 1975, trends acquired a comprehension similar to their current meaning, emphasizing their economic relevance, which coincides not arbitrarily with the birth of mass consumption. The contemporary connotation associates trends to changes and transformations that involve different sociocultural and economic aspects. In turn, fashion trends are expressions of sociocultural tendencies in visual and tactile characteristics applied to fashion products.